Spousal spillovers in the labor market: A structural assessment - Sigurd Mølster Galaasen; Herman Kruse (Norges Bank, 2024)
We explore the importance and nature of elderly couples' labor market interlinkages, and how such linkages shape the response to welfare reforms. To this end, we build a life cycle model with dual-earner households, featuring heterogeneous age gaps, non-separable leisure preferences, and endogenous retirement. To inform key preference parameters, our calibration exploits quasiexperimental evidence of spousal retirement spillovers from a pension reform in Norway. We show that the experimental evidence is highly informative about the degree of non-separability of leisure and that a substantial level of complementarity is required to match the data. Using our calibrated model, we find that the commonly observed tendency of couples to retire together, despite considerable age-gap heterogeneity, can be entirely explained by leisure complementarities. Moreover, comparing to a model with leisure separability reveals that one-third of the long-run labor supply impact of the pension reform is attributed to complementarity. This illustrates the importance of accounting for interdependent decisions when evaluating policy reforms.
hdl:11250/3166779
Keywords: D15; E2; E6; E65; H55; J08; J2; 330; Joint retirement; couples; life cycle; pension reform; leisure complementarity; spousal spillover